Letter (copy) : Repatriation of Basque Children - Tewson, Vincent
1938-02-08 038-0164-001 HVT/FC/EK/539. Secretary's. 8th February, 1938. Mr. W. Short, Newcastle and District Trades Council, Riddell Avenue, Pendower, NEWCASTLE-ON-TYNE, 5. Dear Mr. Short, REPATRIATION OF BASQUE CHILDREN. I have your letter of the 4th instant in regard to the above matter and note that your Council has sent a telegram and letter of protest to the Basque Children's Central Committee. I happen to be Vice-Chairman of the Basque Children's Committee and appreciate the interest of your Council in the children but really, you know, it would be better to enquire into a matter which is reported to you rather than to accept an ex-parte statement with all its implications. The question of repatriation is one of extreme difficulty and it may have been that on the occasion when Mrs. Badsey went through with the children it had not been possible to arrange for representatives to go through to Bilbao which has been the usual practice. It is not usual, however, for the parents to meet the children at the frontier, but they go through to Bilbao and are taken over there. As Mrs. Badsey is closely connected with the Children's Hostel at Tynemouth I know just how she will feel about the children's return and any hitch in arrangements. I have a personal interest in one of the Homes 292/946/38/164(I)